The GridPP DIRAC project: Implementation of a multi-VO DIRAC service. Issue 6 (December 2015) - Bauer, D; Colling, D; Currie, R; Fayer, S; Huffman, A; Martyniak, J; Rand, D; Richards, A
Abstract: The GridPP consortium provides computing support to many high energy physics projects in the UK. As part of this GridPP offers access to a large amount of highly distributed resources across the UK for multiple collaborations. The userbase supported by GridPP includes hundreds of users spanning multiple virtual organisations with many different computing requirements. In order to provide a common interface to these distributed a centralised DIRAC instance has been setup at Imperial College London. This paper describes the experiences learnt from deploying this DIRAC instance and the modifications that have made to support the GridPP use case.